1993
DOI: 10.1021/bi00064a035
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and thermodynamics of the mechanism of interaction of sodium phytate with .alpha.-globulin

Abstract: The precipitation mechanism of alpha-globulin in the presence of myo-inositol hexaphosphate (sodium phytate) was studied in detail. The maximum interaction was found at pH 2.3 where the protein was in a dissociated state having an 8.3S aggregate and a 1.5S monomer. This interaction was predominantly dependent upon the sodium phytate to protein ratio. Velocity sedimentation studies indicated polymer formation due to preferential progressive binding of ligand to polymer, whose size and concentration increased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…This complex formation is a bi-phasic reaction, initially phytate binds and changes the conformation of protein in a rapid step and this is followed by a slower, progressive, aggregation of protein and ultimately the protein-phytate complex precipitates when it exceeds a critical size. Rajendran and Prakash (1993) demonstrated this reaction with sodium phytate and α-globulin; protein-phytate complex formation was maximal at pH 2.3 and dependant upon phytate to protein ratios.…”
Section: Probable Underlying Mechanismsmentioning
confidence: 85%
“…This complex formation is a bi-phasic reaction, initially phytate binds and changes the conformation of protein in a rapid step and this is followed by a slower, progressive, aggregation of protein and ultimately the protein-phytate complex precipitates when it exceeds a critical size. Rajendran and Prakash (1993) demonstrated this reaction with sodium phytate and α-globulin; protein-phytate complex formation was maximal at pH 2.3 and dependant upon phytate to protein ratios.…”
Section: Probable Underlying Mechanismsmentioning
confidence: 85%
“…It is noteworthy that O'Dell & de Boland (33) detected protein -phytate interactions in soya flakes but not in maize germ or sesame meal. In contrast Kies et al (37) reported protein -phytate interactions in maize at pH 2 and Rajendran & Prakash (27) reported interactions between sesame a-globulin and phytate that peaked at pH 2·3. However, O'Dell & de Boland (33) conducted their studies at pH levels of 4·4 and 9·0, so it appears that pH differences in the in vitro systems account for the apparent discrepancies in outcomes and emphasise the importance of pH to protein -phytate interactions.…”
Section: Binary Protein-phytate Complexesmentioning
confidence: 91%
“…The potential capacity of Ca to disrupt binary protein-phytate interactions may explain the diminished amino acid digestibility responses to supplemental phytase at higher Ca concentrations in the Ravindran et al (42) study. According to the Cosgrove (14) and Rajendran & Prakash (27) descriptions of binary complexes, the likelihood is that phytate is 'protected' by a shield of aggregated protein once complex formation takes place and would be less susceptible to hydrolysis by exogenous phytase. Thus phytase essentially prevents de novo complex formation via the prior hydrolysis of phytate and binary complexes may be an important limiting factor on the extent of enzymic degradation of phytate.…”
Section: Binary Protein-phytate Complexesmentioning
confidence: 99%
“…At pH levels below the isoelectric point of protein the polyanionic phytate molecule electrostatically binds with residues of the basic amino acids arginine, histidine and lysine. This initial, rapid step is followed by a progressive protein-protein aggregation that may result in precipitation (Rajendran and Prakash, 1993). The crucial proposition is that phytate-bound protein is refractory to pepsin digestion (Camus and Laporte, 1976;Knuckles et al, 1985Knuckles et al, , 1989.…”
Section: Underlying Mechanismsmentioning
confidence: 99%